Proposed Digital Marketing Strategy And Food Product Assortment To Increase Sales Performance Of Coffee Shop - Aghnarizky Dzulkarnain, Fino; Furinto, Asnan (Fakultas Ekonomi Universitas Gresik, 2023)
This study focuses on the growing food and beverage industry in Indonesia, which contributed considerably to the overall gross domestic product (GDP) of the country and experienced growth of 0.22% in the second quarter of 2020. As people drink more coffee, the coffee shop business has expanded, and Poseidon Coffee in Cikarang is one of the businesses that has benefited from this trend. Despite this, the COVID-19 pandemic had a significant effect on the industry, which resulted in decreasing sales as a direct result of increased government regulations and limitations. Poseidon Coffee's sales have been slowly climbing back up, although they still have not reached the levels they were at before the outbreak. This study seeks to provide recommendations to improve Poseidon Coffee's sales performance by applying digital marketing tactics and expanding their line of food products. These recommendations will be provided as part of this study. The investigation makes use of a thorough methodology, which incorporates such concepts as the Resource Based View, the Segmenting, Positioning, and Targeting model, the Marketing Mix, Porter's Five Forces, Competitor Analysis, and Customer Analysis, amongst others. When developing plans in response to both internal and external analyses, the TOWS Matrix is an invaluable tool. The findings of the research provide significant insights that may be used to address difficulties faced by businesses and increase sales success. Poseidon Coffee intends to capitalize on the growing demand for coffee in Indonesia by using innovative marketing methods in the near future. The company places an emphasis on high-quality products, skilled baristas, and a location that is advantageous for business in order to overcome commercial hurdles. It is vital to engage in promotional activities and social media engagement, in addition to collaborating with local businesses, in order to expand the culinary offers and compete with other businesses that are particularly strong in the area.